Values, religions and education in changing societies - Sporre, Karin; Mannberg, Jan (Springer Netherlands, 2011)
Education is a societal matter and takes place in relation to societal changes. Today, in many countries, it has to grapple with diversity and differences brought about by migration and changes in gender relations. Questions of values, human rights and the role of religions are raised. In this book scholars from Sweden, Norway, Germany, Great Britain, Canada, Namibia and South Africa discuss the issues above. Similarities as well as differences are highlighted. The varied contributors engage in a North-South dialogue. Among the questions addressed are: Can the Scandinavian countries be understood as more religious than their up-to-date, seemingly secularist reputation has led us to believe? How do some European, Muslim, Christian and secular pupils understand the religious education they receive? Could a global citizenship education, with a gendered understanding as an integral part, be accomplished? Diversity and social justice: what does it take to theoretically integrate these two crucial parameters in education, in South Africa, and in Sweden? The role of religious and values education under changing circumstances is explored through the diverse contributions, that also challenge the hegemony of a Western understanding of democracy, among other values. The purpose of this is to assess what could now constitute global educational common ground.